(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
The increased prevalence of non-communicable diseases, especially those associated with poor diets, highlights the need for alternative behavioural measures to promote healthy food intake. Focussing on eating behaviours with awareness and non-judgment improves self-regulation and diet. However, data on its use and effects in Malaysian adults are scarce. Mindful eating (ME), food choice reasons, and health-related well-being among Malaysian adults are examined in this study. The Mindful Eating Questionnaire (MEQ), Food Choice Questionnaire (FCQ), and self-reported well-being indicators were completed by 1,002 respondents. Variable associations were assessed using descriptive and correlation analysis. The results showed no gender difference in total MEQ scores; however, subscales did vary. Men scored higher in awareness and external signals, whereas women scored higher in emotional response and disinhibition. Mindful eating had positive effects on health, mood, sensory appeal, natural content, and weight control. Mindful eating lowers Body Mass Index (BMI) by reducing disinhibition and emotional reactivity. Higher BMI participants were more conscious and sensitive to external signals. Wellness parameters like physical and mental health, lifestyle, and diet were associated with mindful eating. Mindful eating greatly affects healthy food preferences and may improve physical and mental health. The findings support targeted public health and educational interventions to encourage sustainable eating in Malaysian adults.